2020
DOI: 10.11158/saa.25.1.12
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Acaricide resistance and mechanisms in </strong><strong><em>Tetranychus urticae</em></strong><strong> populations from greenhouses in Turkey</strong><strong></strong></p>

Abstract: Turkey has great potential in vegetable production especially in greenhouses. However, plant pests such as Tetranychus urticae Koch can cause significant yield losses with the contribution of suitable climate conditions of greenhouses that allow to fast development of spider mites. Although synthetic acaricides are the most preferred control tools to manage T. urticae populations in Turkey, control failure has often been reported because of its ability to quickly develop resistance. In this study, bifenthrin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…Previous studies reported that the detoxification of bifenthrin in T. urticae was associated with increased esterase activity rather than cytochrome P450s [15,16]. However, in our study, the activity of P450s, GSTs and CarEs increased and could thus play a vital role in bifenthrin resisitance [17,25]. Moreover, the activity of GSTs (R_bft) was significantly higher than that of the susceptible strain (Lab_SS) (Figure 1b), which is in agreement with the work described by Yang et al in 2001 [26].…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies reported that the detoxification of bifenthrin in T. urticae was associated with increased esterase activity rather than cytochrome P450s [15,16]. However, in our study, the activity of P450s, GSTs and CarEs increased and could thus play a vital role in bifenthrin resisitance [17,25]. Moreover, the activity of GSTs (R_bft) was significantly higher than that of the susceptible strain (Lab_SS) (Figure 1b), which is in agreement with the work described by Yang et al in 2001 [26].…”
Section: Discussioncontrasting
confidence: 75%
“…15,16,21 These methods have been used to monitor acaricide resistance of the TSSM in China, Greece, Ethiopia, and Turkey. 15,16,34,35 However, they often have limitations for detecting early resistance when resistance mutations are expected to be at a very low frequency and large numbers of individuals need to be screened. Moreover, since most resistant alleles are located on the diploid nuclear genome, methods applicable to codominant markers are preferable to identify heterozygous genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been established to detect the acaricide resistance of TSSM, such as Sanger sequencing, TaqMan quantitative polymerase chain reaction (qPCR), and droplet digital PCR (ddPCR) 15,16,21 . These methods have been used to monitor acaricide resistance of the TSSM in China, Greece, Ethiopia, and Turkey 15,16,34,35 . However, they often have limitations for detecting early resistance when resistance mutations are expected to be at a very low frequency and large numbers of individuals need to be screened.…”
Section: Introductionmentioning
confidence: 99%
“…Aphis gossypii Glover, 1877 (Hemiptera: Aphididae) is a cotton pest and known as polyphagous species with a broad-spectrum host plant (Cheng et al, 2023). Chemical pesticides, including the commonly used organophosphorus, pyrethroid and carbamates, have been used intensely against various pests, and the resistance problem has been revealed in recent years (Alpkent et al, 2020;Erdoğan et al, 2023). It has been reported that A. gossypii developed resistance to more than 50 active ingredients in Türkiye and around the World (Anonymous, 2023).…”
Section: Introductionmentioning
confidence: 99%